The Role Of Pre-teacher Training Sessions In Enhancing Novice Teachers’ Qualifications (from Theory To Practice) - Anfal Khadidja Dekhil; Hanane Sarnou (The Journal of Studies in Language, Culture and Society, 2024)
Pre-teacher training is a preparation for teaching that paves the way for novice teachers and opens the door to learn and know the vital skills and ideas to teach successfully. The present study investigated the transition of pre-service teachers from theory to practice; in other words, from university life to a full time teaching in a classroom. It discusses the effectiveness of pre-teacher training as a significant step that enables trainees to deal with predictable situations in the classroom, at ITE (Institut Téchnologique de l’Enseignement) of Saida with an exploratory research methodology. Furthermore, it focused on how the training of pre-teachers contributes to forming qualified teachers. Teacher training allows trainees to be in a real situation in their classroom to put into practice what they have learned during their training process as prospect teachers. (i.e. mastering how to apply the different theories, methods and strategies discussed in class). To this end, we have observed trainees, as novice teachers, how they assess and interact with learners based on their psychological side, how they learned to attract their students ‘attention and make them interested in receiving, accepting and memorizing the information. By the end, they will be apt to solve problems in teaching and learning and do action research to improve the necessary skills. Results revealed that pre-teacher training helps trainees work in groups (collaboration) and learn from the former teachers’ experiences (trainers) to enhance professionalism. It also increases the productivity of pre-teachers and their expectations of success.